2010
DOI: 10.1175/2010jas3432.1
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Amplitude Wave Activity and Diffusive Flux of Potential Vorticity in Eddy–Mean Flow Interaction

Abstract: An exact diagnostic formalism for finite-amplitude eddy-mean flow interaction is developed for barotropic and quasigeostrophic baroclinic flows on the beta plane. Based on the advection-diffusion-reaction equation for potential vorticity (PV), the formalism quantifies both advective and diffusive contributions to the mean flow modification by eddies, of which the latter is the focus of the present article. The present theory adopts a hybrid Eulerian-Lagrangian-mean description of the flow and defines finite-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 39 publications
(55 reference statements)
0
91
0
Order By: Relevance
“…Such methods include FDT, to construct LRFs, and lag-regression (Lorenz and Hartmann 2001;Simpson et al 2013b) and finite-amplitude wave-activity (Nakamura and Zhu 2010;Nie et al 2014), to diagnose eddy feedbacks. As an example, in Part 2 of this study, we useM M M to investigate why the LRF constructed using the FDT performs poorly in some cases.…”
Section: Applications Of the Lrf And Efmmentioning
confidence: 99%
“…Such methods include FDT, to construct LRFs, and lag-regression (Lorenz and Hartmann 2001;Simpson et al 2013b) and finite-amplitude wave-activity (Nakamura and Zhu 2010;Nie et al 2014), to diagnose eddy feedbacks. As an example, in Part 2 of this study, we useM M M to investigate why the LRF constructed using the FDT performs poorly in some cases.…”
Section: Applications Of the Lrf And Efmmentioning
confidence: 99%
“…which is based on the hybrid Eulerian-Lagrangian formulation of Nakamura and Zhu (2010), where A is wave activity, K eff is effective diffusivity, Q is potential vorticity, and Y(Q) is equivalent latitude. As noted by these authors, the Eulerian eddy PV flux across latitude Y(Q), [y 1 *q 1 *], includes both advective and diffusive components, while the PV flux across the Q contour (second term on the right-hand side) is purely diffusive.…”
Section: The Short Time Responsementioning
confidence: 99%
“…Much of our understanding of isentropic mixing has been developed by using a quasi-conservative tracer as the meridional coordinate, which separates irreversible mixing from reversible undulation of tracer contours (e.g., Butchart and Remsberg 1986;Nakamura 1995). More specifically, Nakamura (1996) showed that a passive tracer advected by a 2D nondivergent flow with pure horizontal diffusion can be formulated in a diffusive form and that the ''effective diffusivity'' can be defined by the mass flux across the tracer contours.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, Nakamura (1996) showed that a passive tracer advected by a 2D nondivergent flow with pure horizontal diffusion can be formulated in a diffusive form and that the ''effective diffusivity'' can be defined by the mass flux across the tracer contours. Using a passive tracer driven by the nondivergent isentropic winds in the stratosphere and in the upper troposphere, the effective diffusivity can characterize enhanced mixing within the surf zone and mixing barriers at the subtropics and at the polar vortex edge (Haynes and Shuckburgh 2000a,b;Allen and Nakamura 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation